Ultimum Remedium Approach in Resolving Mining Conflicts Based on Local Wisdom of Gorontalo Community - Haritsa; Dharmawati; Sutriani Abubakar (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
This study aims to examine the legal resolution of people's mining conflicts in Gorontalo Province, using the ultimum remedium principle approach guided by the values ​​of Gorontalo local wisdom known as the Dulohupa tradition. The purpose of this study is to analyze the resolution of mining conflicts with the ultimum remedium approach as an effort to resolve mining conflicts that reflect the values ​​of certainty and justice for the community. The method used in this study is socio-juridical research, an approach that studies the reciprocal relationship between law and other social phenomena by obtaining data relevant to the object of research. Based on the results of the study, it shows that there have been 3 major conflicts involving a consortium of mining permit holders and mining community groups during 2023 in Gorontalo Province. The peak of the conflict was the burning of the Pohuwato Regency Regent's Office during the action that ended in riots on Saturday, September 21, 2023, and the determination of 35 representatives of the mining community as perpetrators of the destruction which has now entered the criminal trial stage in court. The conclusion is that the implementation of conflict resolution with this approach has not been running optimally, as indicated by the continued repressive approach in the form of criminal law enforcement against traditional miners. Keywords: Ulltimum Remedium; Mining Conflict; Local Wisdom, Gorontalo.